De novo comparative transcriptome analysis of genes involved in fruit morphology of pumpkin cultivars with extreme size difference and development of EST-SSR markers - Aliki Xanthopoulou (2018)
© 2017 The genetic basis of fruit size and shape was investigated for the first time in Cucurbita species and genetic loci associated with fruit morphology have been identified. Although extensive genomic resources are available at present for tomato (Solanum lycopersicum), cucumber (Cucumis sativus), melon (Cucumis melo) and watermelon (Citrullus lanatus), genomic databases for Cucurbita species are limited. Recently, our group reported the generation of pumpkin (Cucurbita pepo) transcriptome databases from two contrasting cultivars with extreme fruit sizes. In the current study we used these databases to perform comparative transcriptome analysis in order to identify genes with potential roles in fruit morphology and fruit size. Differential Gene Expression (DGE) analysis between cv. ‘Munchkin’ (small-fruit) and cv. ‘Big Moose’ (large-fruit) revealed a variety of candidate genes associated with fruit morphology with significant differences in gene expression between the two cultivars. In addition, we have set the framework for generating EST-SSR markers, which discriminate different C. pepo cultivars and show transferability to related Cucurbitaceae species. The results of the present study will contribute to both further understanding the molecular mechanisms regulating fruit morphology and furthermore identifying the factors that determine fruit size. Moreover, they may lead to the development of molecular marker tools for selecting genotypes with desired morphological traits.